A robust mix design method for self-compacting concrete. (17th October 2022) - Liu, Linghui; Lei, Mingfeng; Gong, Chenjie; Gan, Shuqing; Yang, Zihan; Kang, Lei; Jia, Chaojun
Graphical abstract: Highlights: A theoretical framework for analyzing SCC's fresh behavior was established. Multilevel excess layer model and rheology-based workability criteria were merged. Generalized self-compacting zones reflect the robustness of SCC mix design. A robust mix design method balancing the SCC's content and rheology was proposed. Abstract: Raw material properties greatly influence the workability of self-compacting concrete (SCC). This paper explored a robust approach to realize the mix design of SCC. A theoretical framework, which combines the excess layer composition model and rheology-based workability criteria, was proposed to analyze the fresh behaviors of the concrete. In the framework, the film-thickness-based composition model established the correlation between concrete's content with the film's thickness and the aggregate's characterization. The suspending cell model could quantify the film's separating, bearing, and lubricating effects, therefore characterizing the mixture's flowability and stability. Besides, the derived rheology threshold defined the fresh mixture's flow spread conditions. The framework was experimentally verified, and the experiment-based threshold calibration referring to the slump flow test significantly improved the framework's accuracy. Two generalized self-compacting zones (SCZs) for analyzing the robustness of SCC mix design, under the coordinate of film's thickness and rheology, were theoretically calculated. Through the analysis of the evaluation law of generalized SCZs, the area of the film-thickness-based SCZ and paste-rheology-based SCZ were able to reflect the control reliability of component content and paste rheology in SCC designing. On this basis, a robust mix design method of SCC was proposed by balancing the two ranges. The discussion on the extension of mix design framework to other types of SCC, industrial application, and reinforced structures demonstrated the framework's broad applicability.